Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

prove: (1) cot square A.cosec square B-cot square B.cosec square A= cot squareA-cot squareB (2) 2sin square theta+cos square theta= 2 under root. 2sin theta.cos theta

Asked by sonali garg 11th September 2013, 9:15 PM
Answered by Expert
Answer:

Pls ask one question at a time. The solution to your first question is as follows:

LHS

= cot2A. cosec2B - cot2B. cosec2A

= cot2A. (1 + cot2B) - cot2B. (1 + cot2A)

= cot2A + cot2A cot2B - cot2B - cot2A cot2B

= cot2A - cot2B

= RHS

Answered by Expert 11th September 2013, 10:25 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!